Eurasia a new peace agenda (Contributions to conflict management, peace economics and development, 2005)
Introduction / Majid Tehranian -- Religious challenges to global security / Mark Juergensmeyer -- Nuclear dilemmas in the 21st century / Yuri E. Fedorov -- The role of Russia in global security / Michael D. Intriligator -- Confidence building measures in Asia / Jozef Goldblat -- Western conflict-management as militarism and imperialism / Jan Oberg -- Globalization and world peace / Thomas L. Friedman -- Russian Eurasianism and American exceptionalism / Alexander I. Nikitin -- New Russian identity formation / Alexander Tsypko -- The caspian between conflict and cooperation / Pirouz Mojtahed-Zadeh -- Multiculturalism in crisis : liberal-conformity, Asian values or unforced consensus? / Johan Saravanamuttu -- Relational identity and ethnic conflict resolution in inner Asia / Dru C. Gladney -- Kazakhstans security challenges in a changing world / Rafis Abazov -- Globalization and dialogue among civilizations / Marshall I. Goldman -- Globalization and civilizations / Yuri V. Yakovets -- Universalizing dialogue / Mohammad Taheri -- Resisting global hegemony / Kinhide Mushakoji -- Civilizations and their discontents / Robert Anderson -- Coalition building for peace / Paul van Tongeren, Guido de Graaf Bierbrauwer -- Superterrorism : implications for a new security strategy / Alexei G. Arbatov